The State of Technology in Craniosynostosis. Issue 4 (June 2018) - Safran, Tyler; Viezel-Mathieu, Alex; Beland, Benjamin; Azzi, Alain J.; Galli, Rafael; Gilardino, Mirko
Abstract : Introduction: Craniosynostosis, the premature fusion of ≥1 cranial sutures, is the leading cause of pediatric skull deformities, affecting 1 of every 2000 to 2500 live births worldwide. Technologies used for the management of craniofacial conditions, specifically in craniosynostosis, have been advancing dramatically. This article highlights the most recent technological advances in craniosynostosis surgery through a systematic review of the literature. Methods: A systematic electronic search was performed using the PubMed database. Search terms used were "craniosynostosis" AND "technology" OR "innovation" OR "novel." Two independent reviewers subsequently reviewed the resultant articles based on strict inclusion and exclusion criteria. Selected manuscripts deemed novel by the senior authors were grouped by procedure categories. Results: Following review of the PubMed database, 28 of 536 articles were retained. Of the 28 articles, 20 articles consisting of 21 technologies were deemed as being novel by the senior authors. The technologies were categorized as diagnostic imaging (n = 6), surgical planning (n = 4), cranial vault evaluation (n = 4), machine learning (n = 3), ultrasound pinning (n = 3), and near-infrared spectroscopy (n = 1). Conclusion: Multiple technological advances have impacted the treatment of craniosynostosis. These innovations include improvement in diagnosis and objective measurement of craniosynostosis, preoperative planning, intraoperative procedures, communication between both surgeons and patients, and surgical education.